Učno zavlačevanje pri srednješolcih - Ribič Hederih, Branka; Čagran, Branka (Revija za elementarno izobraževanje, 2014)
Academic Procrastination of Secondary School Pupils. Procrastination is a trait and/or a form of behavior that denotes an individual’s delay in an activity which should be done, and which causes discomfort. In the study we wished to determine the differences between high school students regarding gender, educational programme and learning success of the previous school year in three factors. On a sample of 284 high school students of different Slovenian secondary schools, we found that on average boys show statistically significantly more shortage of learning self-discipline than girls, while girls, on average, significantly more discomfort than boys. Comparison of secondary school students between programmes showed that, on average, gimnazija students show significantly more learning self-discipline than students in secondary technical education. The comparison in relation to different levels of learning success at the end of the previous school year and the factors of procrastination showed, however, no statistically significant differences.
Keywords: procrastination; learning self-discipline; discomfort; resistance to learning; secondary school students